An Integrative Management Protocol in Alcohol Withdrawal (AYUSHDHARA, 2025)
Alcohol use disorders (AUD) affect approximately 283 million people globally, representing 5.1% of the adult population. An estimated 50% of individuals who abruptly cease heavy alcohol consumption experience withdrawal symptoms. These symptoms typically manifest between two hours to four days after cessation of alcohol intake, ranging from mild discomfort to severe complications. Clinical Findings: The patient presented with symptoms characteristic of alcohol withdrawal, including headaches, nausea, tremors, anxiety, hallucinations, and risk of seizures. These manifestations significantly impacted the patient's quality of life, affecting their physical, mental, personal, social, and spiritual well-being. Diagnosis: The condition was diagnosed as Sannipataja Madatyaya according to Ayurvedic principles, which correlates with alcohol withdrawal syndrome as per DSM-5 criteria. Initial assessment using the CIWA-Ar scale showed a score of 15, indicating moderate withdrawal symptoms. Intervention: The treatment protocol consisted of Kharujradi Mantha administration alongside complementary therapies including yoga, meditation, and counselling. The intervention lasted 28 days in a rehabilitation centre, followed by a 45-day observation period. Outcome: The intervention demonstrated significant therapeutic benefits, with CIWA-Ar scale ratings decreasing from 15 to 4 during the treatment period. Complete remission was achieved by the 28th day, with improvements sustained through the 45-day non-interventional observation period and minimal side effects reported. Conclusion: The successful application of Kharujradi Mantha, combined with complementary therapies, offers a promising alternative for managing mild to moderate alcohol withdrawal symptoms. The minimal side effects and sustained improvement suggest that this approach warrants further investigation through controlled clinical studies to validate its effectiveness and establish standardized protocols.